Memotivasi masyarakat ikut berpartisipasi dalam Pemilihan Kepala Daerah di Kabupaten Sinjai - Andi Ima Kesuma; Abdul Rahman; Rifai Rifai (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Rural communities that have been touched by themomentum of democracy need to increase their awareness ofthe participation in the process of regional head electionsthrough political socialization. Political socialization isconsidered important in the process of political life. The aim ofthis program was to find out how to motivate people toparticipate in political succession through regional elections inSinjai Regency. The output of this program was to fostercommunity awareness to participate in creating a peaceful anddemocratic local election. The method used was deliveringpresentation to the public about the importance of participationin realizing a peaceful and democratic election. It was foundthat the understanding of the community in realizing apeaceful and democratic election was still lack. Theparticipants had a high level of enthusiasm in participating thissocialization which was proved by asking various electionrelatedquestions.